Revealed Comparative Advantage: Theoretical Approach and Analysis of the Lithuanian Dairy Sector vis-a-vis the EU-15 - Vitunskienė, Vlada; Serva, Evaldas (Ekonomika, 2006)
The Balassa’s Revealed Comparative Advantage Index is used as one of the basic dimensions of trade multi-dimensionality indicators. We feel that despite their shortcomings. RCA indices provide a useful tool to detect changes of specialisation or revealed comparative (dis)advantage, and also offer additional information on the competitiveness. Revealed comparative advantage can be measured at the global level. at a regional or sub-global level or restricted to the analysis of bilateral trade between just two countries or trading partners.The distribution of RCA indices in 1996-2004 show that Lithuania has strong revealed comparative advantages in the dairy sector and is experiencing a positive evolution in the EU-IS market context. Despite the fairly stable RCA index for the total dairy products over eight years, specifically early 2000s, the variation of RCA indices for each subcategory dairy products (at CN 4-digit or 6-digit level) was greater. Another feature of these indices is that their pattern shows a polarisation over the period. Throughout the years 1996-2004, Lithuania has revealed comparative advantages for four from six product groups at CN 4-digit levels: concentrated or containing milk and cream (CN 0402); whey products (CN 0404); butter and other fats of milk (CN 0405); cheese and curd (CN 0406). From 2003-2004, only one of the six observed groups (at 4-digit level) had a comparative disadvantage. However, the high coefficients of variation for each subcategory (at CN 6-digit level) dairy products reinforce the finding of greater variation of RCA indices over the eight years.It is also important that RCA value calculations are based on observed trade data. Therefore, it is hardly possible to assume that the RCA index is likely to be influenced by trade and other economic intervention policies in the markets such as tariffs. quotas or subsidies, which were pursued between Lithuania and the EU when Lithuania joined the European Union in 2004. Whilst this is an issue that has been extensively researched, the impact on identification of comparative advantage via RCA indices is not yet clear. Although we have not measured the effect of intervention policy on RCA indices, we can still confirm that the Lithuania’s RCA indices in dairy products have almost doubled after the liberalization of trade regime between Lithuania and the European Union in 2004.